ANTARA TAKWA DAN TAKUT (Kajian Semantik Leksikal dan Historis terhadap al-Qurâan) - Affandi, Abdullah; Suud, Muhammad (Jurnal al Hikmah, 2016)
In some approaches that occurs in Islamic studies, there is one essential that the process is seen as the most urgent and influential in the development process itself, namely Islam "approach-Linguistic Semantics". This approach is an effective instrument or method largest species of human existence for operating the various problems of thinking and communicating to the Islamization through a tool known as the language (semantics). The emergence of diverse studies where the Koran as its object is possible, because as the text of the Koran are interpretable, can have many meanings (yahtamil wujuh al-mana) that contains a wide variety of possible interpretations. Where the role of the study of texts was necessary so that the message of the Koran can be absorbed as a whole and applied to life. Thus, this paper will try to analyze the word piety and fear of the Quran by using both lexical semantic approach, and then forwarded by tracing changes in the meanings of words commonly known as historical semantics